Research Trends of Local Wisdom E-LKPD for Newton Law Problem Solving: Tren Penelitian E-LKPD Kearifan Lokal untuk Pemecahan Masalah Hukum Newton - Ananda Mahaputra Iskandar; Ellianawati Ellianawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Problem-solving skills represent a central competency in 21st-century science education, yet Newton’s Laws are often perceived as abstract concepts that are difficult for junior high school students to understand. Specific Background: Digital learning media such as Electronic Student Worksheets (E-LKPD) integrated with local wisdom and supported by deep learning approaches have been increasingly developed to contextualize physics concepts and connect them with students’ cultural experiences. Knowledge Gap: Although numerous studies have explored the development and implementation of E-LKPD integrated with local wisdom and deep learning approaches in Newton’s Laws instruction, a systematic synthesis of research trends, characteristics, and reported findings within this field has not been comprehensively mapped. Aims: This study aims to analyze publication trends, identify research characteristics, and synthesize findings regarding E-LKPD integrated with local wisdom using deep learning approaches for improving junior high school students’ problem-solving skills in Newton’s Laws during the 2021–2025 period. Results: Using a Systematic Literature Review with the PRISMA protocol, twenty selected journal articles from Google Scholar, SINTA, and DOAJ databases were analyzed. The findings reveal an increasing research trend between 2023 and 2025, with dominant research designs including research and development and quasi-experimental studies. Local wisdom contexts range from traditional games, maritime and agricultural activities, cultural arts, architecture, and community practices, while deep learning approaches commonly involve Problem-Based Learning and Project-Based Learning. Novelty: This review provides an integrated synthesis of research patterns and learning design characteristics connecting E-LKPD, local wisdom, and deep learning in Newton’s Laws instruction. Implications: The findings offer guidance for educators and instructional media developers in designing contextual digital learning media that connect physics concepts with cultural contexts to support students’ problem-solving development. Highlights • Publication growth between 2021 and 2025 indicates increasing research attention in contextual physics learning.• Cultural contexts including traditional activities, arts, and community practices provide authentic scenarios for conceptual analysis.• Deep learning models such as PBL and PjBL frequently appear in digital worksheet design for mechanics topics. Keywords E-LKPD; Local Wisdom; Deep Learning; Newton’s Laws; Problem Solving Skills